Towards a New Paradigm: Stabilising Financial Markets - Moritz Schularick; Kaspar Zimmermann (Intereconomics, 2018)
The pre-crisis paradigm focused exclusively on the positive role of finance. The new paradigm takes the other side of finance seriously and arrives at distinctly different trade-offs and regulatory approaches.
Keywords: 330